The Implementation of Indonesian Qualification Framework (IQF) in College Curriculum - Supa'at, Supa'at (International Conference of Moslem Society, 2018)
Indonesian Qualification Framework (IQF) is a current curriculum applied in all universities in Indonesia. This article aims to describe how is the construction of the IQF, the implementation and the learning strategies used to apply KKNI at STAIN Kudus. This research is a descriptive qualitative research through a case study as the research design. The first result showed that the ways to implement KKNI was to determine the profile of graduates and learning outcomes, to select and to arrange the material, to organize and to structure the curriculum subjects, as well as to put together the lesson plan. The second result showed that applying KKNI included several steps consisting of planning the curriculum, planning the learning process and evaluating the learning program. Finally, the last result showed that learning strategies used to implement KKNI was student-centered learning.